DISTANCE EDUCATION LEARNING AND ENGAGEMENT STRATEGIES IN AN ONLINE LEARNING ENVIRONMENT OF THE STUDENTS - Fausto P. Sombilon, Jr (Adisam Publisher, 2024)
This study aimed to determine the level of distance education learning and engagement strategies in an online environment of the students. This study utilized the non-experimental quantitative research design using descriptive technique involving teachers in Sarangani District, Davao Occidental Division, Philippines. The study was conducted on the second semester of school year 2021-2022. Research instruments on distance education learning was used as source of data. Using mean as statistical tool to treat the data, the study showed the following results: distance education learning in terms of instructor support is very high; level of distance education learning in terms of personal relevance is high; the level of engagement strategies in an online learning environment in terms of learner to content, learner to teacher and learner to learner is very high; the overall level of engagement strategies in an online learning environment is very high.